Not everyone gets a trophy : how to manage the millennials - Tulgan, Bruce (Ascent Audio, 2023)
Learn the secrets of managing a unique and productive generation In the newly revised third edition of Not Everyone Gets a Trophy: How to Bring Out the Best in Young Talent, renowned management trainer and business advisor Bruce Tulgan reimagines how to engage with, develop, and retain millennial employees in a time of deep economic disruption. The book offers step-by-step best practices for getting millennials onboard and up-to-speed. You'll learn how to provide them with the context they lack, teach them how to manage themselves and how to be managed, and turn the very best into new leaders. In the book, you'll also find: a renewed focus on every millennial generation, including Generations X, Y, and Z; a new preface about the dramatic generational shift now taking place in the workforce; and updated case studies and examples, as well as brand-new research on first-wave and second-wave millennials. An essential handbook to maximizing the considerable potential of the millennial generations, Not Everyone Gets a Trophy: How to Bring Out the Best in Young Talent will earn a place in the libraries of executives, managers, HR professionals, and other business leaders interested in getting the most out of each and every one of their employees.